Silk Fibroin-Derived N-Doped Carbon Cloth Coupling with Molybdenum Carbide Nanoparticles as a Self-Supported Electrode for Hydrogen Evolution Reaction - Zhang, Wenqin (Langmuir : the ACS journal of surfaces and colloids, 2024)
Handling tons of waste textiles is a big challenge in the textile and apparel industry. The recycling of waste textiles, especially expensive silk fabrics, is of great significance for resource conservation and green, low-carbon cycle development. In addition, the development of precious metal-free electrocatalysts for the hydrogen evolution reaction (HER) remains a major challenge. In this study, molybdenum carbide nanoparticle-decorated carbonized silk fabrics (Mo2CCSF) were fabricated using a simple process, which can be directly employed as an HER electrode. The obtained materials exhibit remarkable electrocatalytic HER performance in acidic media with low overpotential (60 mV at 10 mA/cm2) and long-term stability (more than 24 h). This work will provide a fresh perspective on the treatment of waste silk fabrics and the fabrication of high-performance electrocatalysts